INTEGRASI PERENCANAAN PRIORITAS DAN KAPASITAS SISTEM MRP II DENGAN SISTEM KANBAN MENGGUNAKAN PROMODEL - Aribowo, Budi; -, Natasari (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
An important problem in manufacturing industry is the lack of capacity calculation in theÂ planning of production. In addition, there are a lot of Work in Process (WIP) the production floor,Â subsequently increasing length of waiting time in manufacturing. The authors proposed theÂ implementation of an integrated system of planning priorities and capacities in the MRP II systemÂ (Manufacturing Resource Planning) with the Kanban system to solve this problem. MRP IIÂ systemsâ priority and capacity planning included capacity calculation to evaluate existing planningÂ priorities, and applied Kanban system in the production floor will pull products when necessary.Â The actual system of Soho and Kanban system will be simulated with ProModel software to helpÂ understanding and analysis. From the results, this study concluded that with MRP II systemâÂ priority and capacity planning, companies can plan production according to the design capacity,Â and the plan can be executed fairly well on the production floor with the Kanban system therebyÂ reducing WIP and manufacturing waiting time on the production floor.